Penyadaran Peran Wanita sebagai Tenaga Kerja Sektor Informal Dalam Persamaan Jender - Handayani, M.Th.; Puspa Yusuf, Ria (Jurnal Studi Jender SRIKANDI, 2008)
More than a half of population in Indonesia are women, which is a potential sources for the country. However, they are still discriminated in terms of job opportunity as well as in family role.In Bali, most of woman have a great contribution in family income, particularly in agricultural sector and also in other informal sectors that could bring more income for the families. Due to the fact that Balinese women plays an important role in family income earning, it is interesting to study the awareness of woman labour role in Bali.Even though the awareness of woman labour role has been done by giving some extension services, however, it is still needed more information for women in mass media to extend their awareness about their important role, especially in gender equality.This paper is a library study, therefore it is a general view of some papers written by researchers in woman and gender issues.